Paraguay Agricultural Sector Risk Assessment : Identification, Prioritization, Strategy, and Action Plan - Arce, Carlos; Arias, Diego (World Bank, Washington, DC, 2015)
This report is the result of a World Bank mission that visited Paraguay in June 2013 at the request of the Government of Paraguay. The mission’s objective was to identify, quantify, and prioritize agriculture risks that determine the volatility of agriculture gross domestic product (GDP), based on a methodology to assess sector risks developed by the World Bank. The methodology stipulates a two-phase process. The first phase (risk evaluation), which is in volume one of this report, was reviewed by the government and evaluates the current situation and perspective of agriculture sector risks, starting from the standpoint of supply chains. From here, and based on the identification of the most important risks, given their frequency and severity, a list of possible solutions was produced in addition to the existing public and private programs and policies. This process is completed with a second phase, where an action plan was prepared (volume two) that can be executed in the medium term to reduce sector risks and to contribute to the sustainability of agriculture investments. The significant efforts undertaken by the government to maintain support programs in critical production and trade areas of the sector are recognized, as well as the institutional development to strengthen the response capacity to agriculture risks. Chapter one gives introduction. Chapter two presents information about the agriculture sector and its recent performance is included, allowing to determine the most important supply chains for this risk assessment and to place the relative economic and social importance of the various commodities and production methods in the appropriate context. In chapter three, a comprehensive assessment of production, market, and enabling environment risks is undertaken for the main commercial and family farming supply chains, in addition to livestock. Chapter four shows the repercussions that risks have had in the past, in particular aggregated losses incurred by supply chain actors. Chapter five assesses the impacts of these losses throughout the supply chains and explores the relative vulnerability of the different actors. Chapter six presents the results and ranking of risks, a list of possible solutions jointly with different public initiatives where some identified risks are addressed.